1989
DOI: 10.1002/j.1460-2075.1989.tb08557.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a newly identified endothelial cell mitogen produced by AtT-20 cells.

Abstract: An endothelial cell growth factor with unique specificity for vascular endothelial cells has been purified from the conditioned medium of the AtT‐20 pituitary cell line. This growth factor, which has been characterized as a homodimer composed of two subunits with mol. wts of 23 kd is a potent mitogen for vascular endothelial cells in vitro with activity detectable at 50 pg/ml and saturation at 1 ng/ml. It was also angiogenic in vivo. In contrast with other endothelial mitogens of the fibroblast growth factor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
188
0
8

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(201 citation statements)
references
References 31 publications
(16 reference statements)
3
188
0
8
Order By: Relevance
“…In contrast to TGF-b, which mainly acts through monocyte chemotaxis (Wahl et al, 1987), VEGF is categorized as a direct angiogenic factor, as it stimulates endothelial cell proliferation and migration in the absence of any other cell type (PloueÈ t et al, 1989). Unlike FGF-1 or FGF-2 (Jaye et al, 1986;Abraham et al, 1986), VEGF is a secreted peptide with a typical NH 2 -terminal signal sequence (Leung et al, 1989;Keck et al, 1989;Conn et al, 1990b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to TGF-b, which mainly acts through monocyte chemotaxis (Wahl et al, 1987), VEGF is categorized as a direct angiogenic factor, as it stimulates endothelial cell proliferation and migration in the absence of any other cell type (PloueÈ t et al, 1989). Unlike FGF-1 or FGF-2 (Jaye et al, 1986;Abraham et al, 1986), VEGF is a secreted peptide with a typical NH 2 -terminal signal sequence (Leung et al, 1989;Keck et al, 1989;Conn et al, 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…Among the angiogenic factors, the VEGF (Vascular Endothelial Growth Factor) family displays several properties suggesting a crucial function in tumor angiogenesis (for review see Ferrara, 1993a). VEGF has been isolated from several tumor cell lines (Senger et al, 1983;PloueÈ t et al, 1989;Rosenthal et al, 1990;Conn et al, 1990a,b). VEGF synthesis is dramatically upregulated in high-grade gliomas, de®ned by prominent endothelial cell proliferation (Plate et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…To date, expression of VPF/VEGF has been demonstrated in rodent and human tumor cell lines, in bovine and mouse pituitary-derived cells (Ferrara and Henzel, 1989;Gospodarowicz et al, 1989;Plouet et al, 1989), in rat corpus luteum (Phillips et al, 1990), and recently, in cultured vascular smooth muscle cells (Tischer et al, 1991 (Dvorak et al, 1979) were cultured in DMEM containing 5% calf serum. Guinea pig resident macrophages were harvested from the peritoneal cavity and lungs by flushing with Hanks' balanced salt solution (HBSS).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that vascular endothelial growth factor (VEGF) is a major regulator of physiological blood vessel growth, namely (1) it is a secreted endothelial cell specific mitogen (Ferrara and Henzel, 1989;Gospodarowicz et al, 1989;Plouet et al, 1989), (2) it induces angiogenesis in in vivo test systems (Connolly et al, 1989;Gospodarowicz et al, 1989), and (3) its expression correlates with phases of angiogenesis during embryogenesis and in the female reproductive cycle (Phillips et al, 1990;Breier et al, 1992;Shweiki et al, 1993). The observation that VEGF expression is upregulated in certain tumors, e.g., in glioblastoma (Plate et al, 1992;Shweiki et al, 1992;Phillips et al, 19931, indicated that VEGF may also regulate angiogenesis in tumors.…”
Section: Introductionmentioning
confidence: 99%